Application of Fourier Transform Infrared Spectroscopy for Determining Some Trading Parameters of Palm Oil - Setiowaty, Gabby (1999)
Malaysia is the largest producer and exporter of palm oil products. For trading purposes, iodine value (IV), free fatty acid (FFA), peroxide value (PV) and anisidine value (An V) are some parameters used to check the quality of palm oil. They are normally analyzed based on the chemical methods. However, many of these standard methods are time consuming. Therefore, simpler and faster methods, such as IR spectroscopy are necessary. In this study, Fourier transform infrared (FTIR) calibration models have been developed to correlate the IV, FFA content, PV and AnV in palm oil, that were obtained from the standard methods. In IV determination, a calibration standard was prepared by blending palm stearin and palm superolein. A validation approach yielded a good coefficient of determination (.R2). Subsequently, 42 palm oil samples with IV ranging from 53 to 65 were also investigated using partial least squares (PLS) and principle component regression (peR). The results gave .R2 of 0.94443 to 0.98853. In the FFA determination, a calibration set was prepared by spiking different amount of oleic acid to a series of palm olein. The cross-validation procedure gave R2 of 0.997. In the fourth study, FTIR method to determine PV of palm olein was studied. A wide calibration range of PV was prepared by adding oxidized palm oil into the unoxidized palm olein. The SEP and J?2 gave 0.172 and 0.996, respectively. In the final study, the FTIR spectroscopy was described to predict An V of palm olein. The calibration set was prepared by mixing the thermally oxidized palm olein and the unoxidized palm olein. The precision of this method was shown to he comparable to chemical method used for measurement of AnV. The results of this study showed that FTIR methods can be used as alternative to measure a number of trading parameters m palm oil to replace the tedious, time-consuming chemical method.